Delineating the neurological phenotype in children with defects in the ECHS1 or HIBCH gene. Issue 2 (16th August 2020) - Marti‐Sanchez, Laura; Baide‐Mairena, Heidy; Marcé‐Grau, Anna; Pons, Roser; Skouma, Anastasia; López‐Laso, Eduardo; Sigatullina, Maria; Rizzo, Cristiano; Semeraro, Michela; Martinelli, Diego; Carrozzo, Rosalba; Dionisi‐Vici, Carlo; et al.
Abstract: The neurological phenotype of 3‐hydroxyisobutyryl‐CoA hydrolase (HIBCH) and short‐chain enoyl‐CoA hydratase (SCEH) defects is expanding and natural history studies are necessary to improve clinical management. From 42 patients with Leigh syndrome studied by massive parallel sequencing, we identified five patients with SCEH and HIBCH deficiency. Fourteen additional patients were recruited through collaborations with other centres. In total, we analysed the neurological features and mutation spectrum in 19 new SCEH/HIBCH patients. For natural history studies and phenotype to genotype associations we also included 70 previously reported patients. The 19 newly identified cases presented with Leigh syndrome (SCEH, n = 11; HIBCH, n = 6) and paroxysmal dystonia (SCEH, n = 2). Basal ganglia lesions (18 patients) were associated with small cysts in the putamen/pallidum in half of the cases, a characteristic hallmark for diagnosis. Eighteen pathogenic variants were identified, 11 were novel. Among all 89 cases, we observed a longer survival in HIBCH compared to SCEH patients, and in HIBCH patients carrying homozygous mutations on the protein surface compared to those with variants inside/near the catalytic region. The SCEH p.(Ala173Val) change was associated with a milder form of paroxysmal dystonia triggered by increased energy demands. In a child harbouring SCEH p.(Ala173Val) and the novel p.(Leu123Phe) change, an 83.6% reduction of the protein was observed in fibroblasts. The SCEH and HIBCH defects in the catabolic valine pathway were a frequent cause of Leigh syndrome in our cohort. We identified phenotype and genotype associations that may help predict outcome and improve clinical management.